Validation of the Perceived Performance in Sport Questionnaire - Joao Lourenço; Bartolomé Jesús Almagro; Pedro Sáenz-López Buñuel (Federación Extremeña de Balonmano; University of Extremadura, 2018)
This study had as purpose the description of the Perceived Performance in Sport Questionnaire process, which aims to assess the performance perception of young athletes in competition sports and prove its criteria validity. The total sample comprised 470 federated athletes, of which 362 were male and 108 female, aged from 13 to 20 years old. To test the instrument, content validation (by experts) was applied as well as the exploratory factorial analysis and the internal consistency (reliability), the temporal stability, the confirmatory factor analysis and linear regression. The results showed that the questionnaire had monofactorial structure, satisfactory internal consistency (α=.88) and test/re-test reliability (r=.94; p<.05) and the confirmatory factor analysis presented adequate adjustment indicators (X2=14.25, p=.01, x2/g.l.=2.85, CFI=.98, IFI=.98, TLI=.97, RMSEA=.08, SRMR=0.03). In conclusion we attested the criteria validity, through positive and significant prediction, of the competences necessity satisfaction and the self-determined motivation over the athletes' performance. In sum, the results allow us to conclude that the Portuguese version of the Perceived Performance in Sport Questionnaire is a valid and reliable tool.